Intravitreal ranibizumab for myopic choroidal neovascularization: 12-month results - Silva, RM (2014)
PURPOSE: The purpose of this study was to evaluate the safety and efficacy of intravitreal ranibizumab after 12 months in the treatment of choroidal neovascularization secondary to pathologic myopia. METHODS: This was a prospective, multicenter, consecutive, nonrandomized, interventional case series. The study included 34 eyes of 32 patients with choroidal neovascularization secondary to pathologic myopia; 13 eyes had previous photodynamic therapy, and 21 eyes had no previous treatment. The patients were followed for > or = 12 months. Best-corrected visual acuity, optical coherence tomography, and the presence of metamorphopsia were assessed monthly. RESULTS: Mean visual acuity improved 8 letters from baseline to 12-month follow-up, and the difference was statistically significant (P < 0.001): 100% of the eyes lost <3 lines on the Early Treatment Diabetic Retinopathy Study chart, 24% of the eyes improved > or = 3 lines, 44% improved > or = 2 lines, 65% improved > or = 1 line, and 79% improved > or = 0 lines. Central retinal thickness decreased significantly from baseline to the 12-month follow-up (P < 0.01). A mean of 3.6 treatments were performed during the 12-month follow-up, and no systemic or ocular side effects were registered during that time. CONCLUSION: One-year results of intravitreal ranibizumab for myopic choroidal neovascularization are very promising. Additional prospective studies are necessary to better determine long-term efficacy and safety.